Sound Transmission Loss of a Double-Leaf Solid-Microperforated Partition Under Normal Incidence of Acoustic Loading - Putra, Azma; Ayob, Md Razali (International Islamic University Malaysia, 2011)
The micro-perforated panel (MPP) is recently well-known as an alternative ‘green‘ sound absorber replacing the conventional porous materials. Constructed from a solid panel which provides a non-abrassive structure and also an optically attractive surface, there gives a feasibility to implement such a panel inside a vehicle cabin. This paper is the preliminary study to investigate the sound transmission loss (TL) of a solid panel coupled with a micro-perforated panel to form a doube-leaf partition which is already known as a lightweigth stucture for noise insulation in vehicles and buildings. The mathematical model for the TL subjected to normal incidence of acoustic excitation is derived. The results show that its performance substantially improves at the troublesome frequency of mass-air-mass resonance which occurs in the conventional double-leaf solid partition. This is important particularly for the noise source predominant at low frequencies. This can also be controlled by tuning the hole size and number as well as the air gap between the panels.